An Arduino kit for learning mechatronics and its scalability in semester projects - Chancharoen, Ratchatin; Sripakagorn, Angkee; Maneeratana, Kuntinee (2014 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE), 2014)
Arduino kits were used in place of general microcontrollers in a mechatronics course. The hand-on learning environment were mostly self-learned with provided learning kits, tutorials and examples from online resources with lecturers as facilitators. Efficient learning could be achieved with 20-30 students in groups of 4 or 5 against 1 lecturer. The theory was assessed by a written exam from which comparable performances to previous years were observed. The learning kits were also used for the semester project in which students had a limited budget for parts and access to a small-scale manufacturing facility.